GMAT Question of the Day: Daily via email | Daily via Instagram New to GMAT Club? Watch this Video

 It is currently 22 Jan 2020, 00:42

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# For which of the following functions is g(c-d) = g(c) - g(d)

Author Message
TAGS:

### Hide Tags

Intern
Joined: 25 Dec 2012
Posts: 25
For which of the following functions is g(c-d) = g(c) - g(d)  [#permalink]

### Show Tags

11 Feb 2013, 10:09
2
13
00:00

Difficulty:

35% (medium)

Question Stats:

69% (01:44) correct 31% (01:37) wrong based on 437 sessions

### HideShow timer Statistics

For which of the following functions is g(c-d) = g(c) - g(d) for all positive numbers c and d?

A g(x) = x^3
B g(x) = x+5
C g(x) = $$\sqrt{3x}$$
D g(x) = 5x
E g(x) 15/x

Sometimes I read a problem 5 times in a row... and I still cannot understand what the question is asking. This was one of those...
EMPOWERgmat Instructor
Status: GMAT Assassin/Co-Founder
Affiliations: EMPOWERgmat
Joined: 19 Dec 2014
Posts: 15958
Location: United States (CA)
GMAT 1: 800 Q51 V49
GRE 1: Q170 V170
Re: For which of the following functions is g(c-d) = g(c) - g(d)  [#permalink]

### Show Tags

14 Jan 2015, 23:50
7
7
Hi All,

In these types of "function" questions, you can TEST VALUES (especially really simple ones) to find the correct answer.

Let's TEST...
C = 2
D = 1

The question asks us to find the equation that gives us the same result when...

g(2-1) = g(1) is calculated

and when

g(2) - g(1) is calculated

g(1) = 1^3 = 1
g(2) - g(1) = 2^3 - 1^3 = 8 - 1 = 7
1 does NOT = 7

g(1) = 1+5 = 6
g(2) - g(1) = (2+5) - (1+5) = 7 - 6 = 1
6 does NOT = 1

g(1) = \sqrt{3}
g(2) - g(1) = \sqrt{6} - \sqrt{3} = \sqrt{3}(\sqrt{2} - 1)
\sqrt{3} does NOT = \sqrt{3}(\sqrt{2} - 1)

g(1) = 5(1) = 5
g(2) - g(1) = 5(2) - 5(1) = 10 - 5 = 5
5 DOES = 5

g(1) = 15/1 = 15
g(2) - g(1) = 15/2 - 15/1 = -15/2
15 does NOT = -15/2

GMAT assassins aren't born, they're made,
Rich
_________________
Contact Rich at: Rich.C@empowergmat.com

The Course Used By GMAT Club Moderators To Earn 750+

souvik101990 Score: 760 Q50 V42 ★★★★★
ENGRTOMBA2018 Score: 750 Q49 V44 ★★★★★
Manager
Joined: 09 Feb 2013
Posts: 111
Re: For which of the following functions is g(c-d) = g(c) - g(d)  [#permalink]

### Show Tags

11 Feb 2013, 10:18
5
1
exploringm wrote:
For which of the following functions is g(c-d) = g(c) - g(d) for all positive numbers c and d?
A g(x) = x^3
B g(x) = x+5
C g(x) = $$\sqrt{3x}$$
D g(x) = 5x
E g(x) 15/x

Sometimes I read a problem 5 times in a row... and I still cannot understand what the question is asking. This was one of those...

This problem arises because in such type of questions the original function is not given. Instead, we have to find a function which can satisfy the constraint mentioned in the question.
Constraint--> g(c-d) = g(c) - g(d)--->(1), where (c-d), c, d are the values of x.
I am directly putting the value in the answer. You can verify the incorrect option by yourself.

Function as per option D is --->g(x) = 5x
Put the value of x = (c-d), we get --->g(c-d) = 5 (c-d) = 5c - 5d----(LHS)
Put the value of x = c, we get --->g(c) = 5 (c) = 5c ----(RHS)
Put the value of x = d, we get --->g(d) = 5 (d) = 5d----(RHS)

Equate RHS & LHS we get--> 5c - 5d = 5c - 5d
Thus equal.

Emma
##### General Discussion
Manager
Joined: 04 Mar 2013
Posts: 64
Location: India
Concentration: General Management, Marketing
GPA: 3.49
WE: Web Development (Computer Software)
Re: For which of the following functions is g(c-d) = g(c) - g(d)  [#permalink]

### Show Tags

04 Jul 2013, 19:48
1
1
exploringm wrote:
For which of the following functions is g(c-d) = g(c) - g(d) for all positive numbers c and d?

A g(x) = x^3
B g(x) = x+5
C g(x) = $$\sqrt{3x}$$
D g(x) = 5x
E g(x) 15/x

Sometimes I read a problem 5 times in a row... and I still cannot understand what the question is asking. This was one of those...

put c = 3 and d = 2 or directly substitute c and d

we get option D,
Manager
Joined: 24 Sep 2012
Posts: 81
Location: United States
GMAT 1: 730 Q50 V39
GPA: 3.2
WE: Education (Education)
Re: For which of the following functions is g(c-d) = g(c) - g(d)  [#permalink]

### Show Tags

16 Feb 2013, 13:21
In such questions these are the steps I find useful!!

1) The first step is to check whether you could solve the expression stated in the question( in case the expression is too long) or substitute the expression into the solutions in some manner so as to solve it quickly. If so, this is the quickest way out and usually with a little bit of practice, you can start judging whether this step would work or not before you place your pen on the paper to solve the question.

2) The next method is to find whether the solutions can be substituted into the original expression in some way that is fast and quick. This usually takes some time and hence, mostly does not work. However, if the answer options involve numbers instead of expressions, this might work better.

This method is only for those questions in which the answer options and the questions both contain expressions.

3) You could try substitution of base values to confirm.

.
exploringm wrote:
For which of the following functions is g(c-d) = g(c) - g(d) for all positive numbers c and d?

A g(x) = x^3
B g(x) = x+5
C g(x) = $$\sqrt{3x}$$
D g(x) = 5x
E g(x) 15/x

Sometimes I read a problem 5 times in a row... and I still cannot understand what the question is asking. This was one of those...
Intern
Joined: 20 Apr 2013
Posts: 17
Concentration: Finance, Finance
GMAT Date: 06-03-2013
GPA: 3.3
WE: Accounting (Accounting)
Re: For which of the following functions is g(c-d) = g(c) - g(d)  [#permalink]

### Show Tags

30 Apr 2013, 22:54
1
Why is option C Wrong
\sqrt{3(c-d)} = \sqrt{(3c)}-\sqrt{(3d)}
Senior Manager
Joined: 16 Dec 2011
Posts: 283
Re: For which of the following functions is g(c-d) = g(c) - g(d)  [#permalink]

### Show Tags

30 Apr 2013, 23:08
Rajkiranmareedu wrote:
Why is option C Wrong
\sqrt{3(c-d)} = \sqrt{(3c)}-\sqrt{(3d)}

Option C says g(x) = $$\sqrt{3x}$$

So, g(c-d) = $$\sqrt{c-d}$$
g(c) = $$\sqrt{c}$$
g(d) = $$\sqrt{d}$$

We cannot say that $$\sqrt{c-d}$$ = $$\sqrt{c}$$ - $$\sqrt{d}$$ for all values of c and d
So we cannot say that g(c-d) = g(c) - g(d) for all values of c and d.

Thus, option c is wrong.
SVP
Status: The Best Or Nothing
Joined: 27 Dec 2012
Posts: 1725
Location: India
Concentration: General Management, Technology
WE: Information Technology (Computer Software)
For which of the following functions is g(c-d) = g(c) - g(d)  [#permalink]

### Show Tags

21 Jan 2015, 20:59
A g(x) = x^3

Power of "x" is changed, so IGNORE

B g(x) = x+5

"x" is added by constant, so IGNORE

C g(x) = \sqrt{3x}

Power of "x" is changed, so IGNORE

D g(x) = 5x

"x" is multiplied by constant 5, so required result is true

E g(x) 15/x

$$\frac{15}{x} = 15 * x^{-1}$$

Again power of "x" is changed, so IGNORE

Manager
Joined: 18 Jun 2017
Posts: 58
Re: For which of the following functions is g(c-d) = g(c) - g(d)  [#permalink]

### Show Tags

18 Aug 2017, 01:01
Plug in values as c=4 and d=2
which will bring down the funtion in problem statement to g(2)=g(4)-g(2).
Now substituting the values in the option available as per the above equation LHS=RHS is option D.
Director
Joined: 04 Sep 2015
Posts: 675
Location: India
WE: Information Technology (Computer Software)
Re: For which of the following functions is g(c-d) = g(c) - g(d)  [#permalink]

### Show Tags

22 Aug 2017, 11:09
For which of the following functions is g(c-d) = g(c) - g(d) for all positive numbers c and d?

A g(x) = x^3
B g(x) = x+5
C g(x) = 3x−−√3x
D g(x) = 5x
E g(x) 15/x

well its jus asking if they are the same or not, for that just substitute the value and we can find out.
Option D is the corect answer.
Target Test Prep Representative
Status: Founder & CEO
Affiliations: Target Test Prep
Joined: 14 Oct 2015
Posts: 9092
Location: United States (CA)
Re: For which of the following functions is g(c-d) = g(c) - g(d)  [#permalink]

### Show Tags

14 Sep 2018, 17:49
exploringm wrote:
For which of the following functions is g(c-d) = g(c) - g(d) for all positive numbers c and d?

A g(x) = x^3
B g(x) = x+5
C g(x) = $$\sqrt{3x}$$
D g(x) = 5x
E g(x) 15/x

We can let c = 2 and d = 1, and thus we are solving for both sides being equal when:

g(1) = g(2) - g(1)

Starting with answer choice E, we have 15/x:

g(1) = 15/1 = 15

g(2) = 15/2 = 7.5

g(2) - F(1) = 7.5 - 15 = -7.5

Since 15 does not equal -7.5, E is not correct.

Moving to D, we have 5x:

g(1) = 5 x 1 = 5

g(2) = 5 x 2 = 10

g(2) - g(1) = 10 - 5 = 5

Since 5 does equal 10 - 5, D might be correct.

For answer choice C, we have √3x:

g(1) = √(3*1) = √3

g(2) = √(3*2) = √6

Since √3 does not equal √6 - √3 = √3(√2 - 1), C is not correct.

For answer choice B, we have x + 5:

g(1) = 1 + 5 = 6

g(2) = 2 + 5 = 7

Since 6 does not equal 7 - 6 = 1, B is not correct.

For answer choice A, we have x^3:

g(1) = 1

g(2) = 8

Since 1 does not equal 8 - 1 = 7, A is not correct.

Since the only answer choice that is definitely not incorrect is D, it must be the correct answer.

_________________

# Scott Woodbury-Stewart

Founder and CEO

Scott@TargetTestPrep.com
181 Reviews

5-star rated online GMAT quant
self study course

See why Target Test Prep is the top rated GMAT quant course on GMAT Club. Read Our Reviews

If you find one of my posts helpful, please take a moment to click on the "Kudos" button.

Non-Human User
Joined: 09 Sep 2013
Posts: 13993
Re: For which of the following functions is g(c-d) = g(c) - g(d)  [#permalink]

### Show Tags

18 Nov 2019, 03:56
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________
Re: For which of the following functions is g(c-d) = g(c) - g(d)   [#permalink] 18 Nov 2019, 03:56
Display posts from previous: Sort by